PREVENTION OF HYPERTENSION BY USING FRUIT THROUGH ONLINE WRITING - Salbya Datukarama; Frezy Paputungan; Sri Yulan Umar (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
According to Sarwono (2011), the emergence of problems in adolescent reproductive health is a consequence. Suddenly pregnant and there will also be ridicule of rejection (in F.Paputungan: 2023). Hypertension is a health problem throughout the world and is one of the main risk factors for cardiovascular disease. Hypertension is also referred to as a non-communicable disease, because hypertension is not transmitted from person to person. Non-communicable diseases are chronic diseases that cannot be transmitted to other people. Non-communicable diseases are still a health problem of concern in Indonesia today. This is because the emergence of PTM is generally caused by the lifestyle of each individual who pays little attention to health (Riskesdas, 2018). Data released by WHO (2018) shows that around 26.4% of the world's population suffers from hypertension, with a ratio of 26.6% of men and 26.1% of women. Approximately 60% of hypertension sufferers are in developing countries, including Indonesia. According to data released by the Ministry of Health, hypertension and other heart diseases account for more than a third of the causes of death, with hypertension being the second cause of death after stroke. Hypertension is defined as an increase in systolic blood pressure greater than or equal to 140 mmHg, and an increase in diastolic blood pressure greater than or equal to 90 mmHg. Hypertension is the main cause of heart failure, stroke and kidney failure. Many factors can influence blood pressure, both factors that can be changed and not. One factor that can be changed is lifestyle, where a person's lifestyle is greatly influenced by their knowledge of a disease. And the factor that cannot be changed is genetic.